2021
DOI: 10.1007/s00187-021-00325-4
|View full text |Cite
|
Sign up to set email alerts
|

Banks’ risk culture and management control systems: A systematic literature review

Abstract: Over ten years of a debate about the best ways to make banks safer have led to the conclusion that improving their risk culture is one venue to achieve this goal. Consequently, different disciplines discuss topics related to risk culture from varying methodological angles. This effort of many scholars provides a rich basis of theoretical and empirical evidence to guide business practice and improve regulation. However, the application of many approaches and methods can result in fragmentation and loss of a com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 123 publications
0
11
0
1
Order By: Relevance
“…Most of the time, banks play the role of an intermediary between their clientele, who need financial resources, and those who themselves need such resources. Banks must manage risks associated with financial operations just as they handle risks associated with any other business operation (Kunz & Heitz, 2021). In addition, banks are crucial to a country's economic development because they facilitate the availability of capital and lend backing to businesses and initiatives that can contribute to that development.…”
Section: Financial Technology Innovationmentioning
confidence: 99%
“…Most of the time, banks play the role of an intermediary between their clientele, who need financial resources, and those who themselves need such resources. Banks must manage risks associated with financial operations just as they handle risks associated with any other business operation (Kunz & Heitz, 2021). In addition, banks are crucial to a country's economic development because they facilitate the availability of capital and lend backing to businesses and initiatives that can contribute to that development.…”
Section: Financial Technology Innovationmentioning
confidence: 99%
“…Pengelolaan risiko pada perbankan telah mengalami peningkatan sejalan dengan perkembangan industri keuangan secara keseluruhan (Kunz and Heitz 2021). Dalam beberapa tahun terakhir, perbankan mulai memahami pentingnya pengelolaan risiko untuk menjaga stabilitas dan kelangsungan bisnis.…”
Section: Pendahuluanunclassified
“…They also suggested that ownership structure and its impact on the performance of banks need to be investigated further. Kunz and Heitz (2021) performed a systematic literature review of banks' risk culture and management control systems. They interpreted the findings through the theoretical lens of management control research and synthesized them to a comprehensive model.…”
Section: Empirical Reviewmentioning
confidence: 99%